2022
DOI: 10.61310/mndjstea.0954.22
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysical and Nutrient Characteristics of Degraded Soils in Sta. Rita, Samar, Philippines

Jessie R. Sabijon,
Victor B. Asio

Abstract: The productivity of degraded soils greatly depends on a good understanding of their characteristics. Hence, the study was conducted to determine the morphological, physical and chemical characteristics of degraded soils in Sta. Rita, Samar, Philippines. Four representative soil profiles located in different physiographic positions were examined, characterized and sampled. The examination was conducted using a pit measuring approximately 1-m wide and 1-m depth. Soil samples were collected from each horizon, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This study observed no clear trend (p > 0.05) in WHC values between the different vegetation patches (Figure 3). Although WHC ranged from 41.88 to 46.68%, and within the WHC range of clayey (Moody and Cong, 2008) and degraded soils (Asio et al, 2015;Sabijon and Asio, 2022), results corroborated the observation of Asio et al (2015) as WHC being not a desirable indicator of soil degradation due to its dependence to soil texture and a stable soil property.…”
Section: Whcsupporting
confidence: 64%
See 2 more Smart Citations
“…This study observed no clear trend (p > 0.05) in WHC values between the different vegetation patches (Figure 3). Although WHC ranged from 41.88 to 46.68%, and within the WHC range of clayey (Moody and Cong, 2008) and degraded soils (Asio et al, 2015;Sabijon and Asio, 2022), results corroborated the observation of Asio et al (2015) as WHC being not a desirable indicator of soil degradation due to its dependence to soil texture and a stable soil property.…”
Section: Whcsupporting
confidence: 64%
“…Navarrete et al (2013) also reported pH levels of 5.12 and 5.48 from the studied degraded soils in Ormoc and Baybay, Leyte, respectively. Calubaquib et al (2016) and Sabijon and Asio (2022) reported a pH range of 4.5 to 5.4 and 5.0 to 7.0 in the studied degraded soils in Luzon and Samar, respectively. The moderate to strong acidity condition means that this degraded upland had soil fertility problems regarding nutrient availability, micronutrient toxicity and microbial activity (Bohn et al, 2001).…”
Section: Soil Phmentioning
confidence: 81%
See 1 more Smart Citation